Significant effect of HIV/HAART on oral microbiota using multivariate analysis - Griffen, Ann L. (Sci Rep, 2019)
Persons infected with HIV are particularly vulnerable to a variety of oral microbial diseases. Although various study designs and detection approaches have been used to compare the oral microbiota of HIV-negative and HIV-positive persons, both with and without highly active antiretroviral therapy (HAART), methods have varied, and results have not been consistent or conclusive. The purpose of the present study was to compare the oral bacterial community composition in HIV-positive persons under HAART to an HIV-negative group using 16S rRNA gene sequence analysis. Extensive clinical data was collected, and efforts were made to balance the groups on clinical variables to minimize confounding. Multivariate analysis was used to assess the independent contribution of HIV status. Eighty-nine HIV-negative participants and 252 HIV-positive participants under HAART were sampled. The independent effect of HIV under HAART on the oral microbiome was statistically significant, but smaller than the effect of gingivitis, periodontal disease, smoking, caries, and other clinical variables. In conclusion, a multivariate comparison of a large sample of persons with HIV under HAART to an HIV-negative control group showed a complex set of clinical features that influenced oral bacterial community composition, including the presence of HIV under HAART.